SURFACE MODIFICATION OF TEMPO-MEDIATED CELLULOSE NANOFIBRIL WITH OCTADECYLAMINE - Nanang Masruchin; Arif Nuryawan; Wida Banar Kusumaningrum; Sudarmanto Sudarmanto; Lilik Astari; Putri Amanda; Resti Marlina; Lisman Suryanegara (Jurnal Sains Materi Indonesia, 2019)
In this study, surface modification of 2,2,6,6-tetramethylpiperidine-1-oxyl radical TEMPO-cellulose nanofibrils (TCNF) was obtained by 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N–hydroxysuccinimide (NHS)-mediated system. The carboxylate groups on TCNF surface was replaced by conjugation of octadecylamine (ODA). The conversion of the carboxylate groups on CNF into amide I and II groups was confirmed by attenuated transform reflectance-infrared (ATR-FTIR) and elemental analysis study. Further, decarboxylation of TCNF at higher temperature was hindered by the presence of amide groups resulted in the higher thermal stability of TCNF as observed by thermogravimetry analysis (TGA). These results suggested the possibility of modifying surface negatively charged of TCNF with conjugated amine groups into thermally stable nanocellulose.